Visibility of news items on Twitter and Facebook: comparative analysis of the most replicated news in Europe and the Americas - Zago, Gabriela da Silva; Bastos, Marco Toledo (Brazilian journalism research, 2013)
This paper identifies and compares the top replicated news items on Twitter and Facebook, on news websites from Brazil, Germany, Spain, the United States and United Kingdom. The data includes 8 of the newspapers with the largest circulation in the 5 countries, totaling 40 outlets. The volume of “retweets” and “likes” was used as a metric for representing the visibility of news items. Links posted on Twitter and messages posted by newspapers on Facebook were collected for a period of two weeks during October 2012. Content analysis was carried out for the top 25 replicated messages in each social network, which uncovered significant cultural traits and editorial differences across countries, based upon the content that circulated on social networks during the period. The results confirm users’ perceptions of social networking sites, with Facebook being used largely for entertainment and recreation, and Twitter for covering political, economic, and social events.